EKSPLORASI ORGANIZATION CITIZENSHIP BEHAVIOR DAN HUBUNGANNYA DENGAN SPIRITUAL LEADERSHIP, SELF EFFICACY DAN LOCUS OF CONTROL - Setiawan, Ady; Indriawati, Arlisa (JURASIMA, 2024)
This study analyzes the role of Spiritual Leadership, self-efficacy, and locus of control on Organizational Citizenship Behavior using quantitative methods in multiple linear regression analysis, involving 50 respondents. The results of the study indicate that there is a significant role of the variables of Spiritual Leadership self-efficacy, and locus of control simultaneously on Organizational Citizenship Behavior. There is a significant influence of the Spiritual Leadership variable on the Organizational Citizenship Behavior variable at the East Java Provincial Transportation Agency. There is a significant influence of the self-efficacy variable on the Organizational Citizenship Behavior variable at the East Java Provincial Transportation Agency. There is a significant influence of the locus of control variable on the Organizational Citizenship Behavior variable at the East Java Provincial Transportation Agency. The simultaneous determination value (R square) of 0.892 means that the variation in changes in Organizational Citizenship Behavior is influenced by Spiritual Leadership self-efficacy, locus of control, by 89.2% while the remaining 10.8% is influenced by other variables not studied